2022
DOI: 10.3390/mi13010104
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Integration of 3D C-MEMS Microelectrodes with Bipolar Exfoliated Graphene for Label-Free Electrochemical Cancer Biomarkers Aptasensor

Abstract: The electrochemical label-free aptamer-based biosensors (also known as aptasensors) are highly suitable for point-of-care applications. The well-established C-MEMS (carbon microelectromechanical systems) platforms have distinguishing features which are highly suitable for biosensing applications such as low background noise, high capacitance, high stability when exposed to different physical/chemical treatments, biocompatibility, and good electrical conductivity. This study investigates the integration of bipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This has been observed in several studies that developed label-free C-MEMS aptasensors through the introduction of carbon-rich materials (e.g., reduced graphene oxide, SU-8 photoresist) for early detection of cancer biomarkers. In both studies, electrochemical characterisation revealed a comparable linear range of detection [114,115].…”
Section: Diagnostic Applicationsmentioning
confidence: 84%
See 1 more Smart Citation
“…This has been observed in several studies that developed label-free C-MEMS aptasensors through the introduction of carbon-rich materials (e.g., reduced graphene oxide, SU-8 photoresist) for early detection of cancer biomarkers. In both studies, electrochemical characterisation revealed a comparable linear range of detection [114,115].…”
Section: Diagnostic Applicationsmentioning
confidence: 84%
“…Carbon-NEMS/C-MEMS involves the patterning of carbon-based materials followed by pyrolysis in an oxygen-free environment. According to Forouzanfar, et al [114], C-NEMS/MEMS approaches offer facile fabrication of electrochemical-based sensors equipped with tailored glassy-like carbon structures (e.g., three-dimensional micropillar, microchannel, microarray) and active surfaces for functionalization due to the high presence of carboxyl groups (-COOH). This has been observed in several studies that developed label-free C-MEMS aptasensors through the introduction of carbon-rich materials (e.g., reduced graphene oxide, SU-8 photoresist) for early detection of cancer biomarkers.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
“…Moreover, electrochemical biosensors utilizing graphene and other 2D materials have shown great potential for detecting biomarkers associated with hematological malignancies like leukemia, lymphoma, and multiple myeloma. These biosensors offer a wide linear range, a low detection limit, high sensitivity, excellent selectivity, and cost-effectiveness [ 40 ].…”
Section: Advantages Of 2d Materials and Cellulose In Biosensorsmentioning
confidence: 99%